Examination of Credence and Noncredence Service Advertisement Strategies in the United States and India. Issue 3 (3rd July 2018) - Utkarsh,
ABSTRACT: This study investigated the differences in advertising strategies of services marketers in two culturally distinct markets by classifying services on the basis of search, experience, and credence attributes. A content analysis of 221 service print ads revealed that the type of service serves an important role for using appeal and service quality cues in service ads. In the case of credence services, ads in India are more likely to contain a reliability dimension of the service quality, and ads in the United States are more likely to utilize responsiveness cues.